Analisis Pengaruh Arus Kas Operasi dan Laba Akuntansi Terhadap Return Saham Perusahaan Sektor Rokok yang Terdaftar Dibursa Efek Indonesia Tahun 2016-2020 - Fristy, Anne Monika; K, Kardi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The purpose of this study is to determine the effect of operating cash flow and accounting profit on stock returns on the IDX. The data used in this study are secondary data obtained from the company's annual financial reports in the Indonesia Capital Market Directory (ICMD) and the Indonesia Stock Exchange (IDX). The sample used in this study was 4 companies that had met the research criteria during 2016-2020. The results of the operating cash flow variable have a significant effect on stock returns. From the regression results, it is known that the t-count value is 1.557> t table 2.101 with a sig value of 0.000, which means sig <0.05, accounting profit has a significant effect on stock returns. From the regression results, it is known that the t-count value is 7.159> t table 2.101 with a sig value of 0.000, which means sig <0.05. but in simulation, operating cash flow and accounting profit have a significant positive effect on stock returns.